Hadrian's wall an historic landscape - Woodside, Robert; Crow, James (<<The>> National Trust, 1999)
The authors examine the impact of human activity in the area of Hadrian's Wall, from its Roman inception to the present day. They consider the different elements of the wall's construction and its role in settlement, agriculture and the local economy.
Keywords: Fortification, Roman -- England; Hadrian's Wall (England); Landscape changes -- England, Northern; Landscapes -- England, Northern; Romans -- England; Archäologie; Geschichte; Hadrian's Wall (England) - History; Northumberland (England) - History; Großbritannien; England -- Antiquities, Roman; England, Northern -- Historical geography; Great Britain -- History, Military -- 55 B.C.-449 A.D; Hadrianswall